Carbon footprint and energetic analysis of tomato production in the organic vs the conventional cropping systems in Southern Italy. (20th May 2019) - Ronga, Domenico; Gallingani, Tommaso; Zaccardelli, Massimo; Perrone, Domenico; Francia, Enrico; Milc, Justyna; Pecchioni, Nicola
Abstract: Sustainable agriculture aims to reduce its environmental impact. In this research, the carbon footprint and energetic analysis have been performed for three consecutive years to investigate the actual environmental impact of processing tomato production, in the organic (OS) vs the conventional cropping systems (CS), in a specialized Mediterranean area in Southern Italy. The global warming potential (GWP, in term of kg CO2 -eq) and primary energy demand (PED, in term of MJ) of processing tomato produced in the two systems (average of three years) were compared in this study. Our results indicate that GWP was on average + 22% in the OS than in CS using 1 ton of marketable fresh fruits as FU. On the other hand, GWP recorded in the OS was, on average, −40% compared to the CS, if 1 ha was considered. A similar impact was registered for PED. The OS showed +28% vs −38% of PED than the CS, using 1 t of marketable fresh fruit vs 1 ha. Pesticide and fungicide applications and soil tillage had the highest impacts among management inputs on GWP and PED, for both farming systems. Hence, the environmental efficiency of these practices could be largely improved in the production of processing tomato aiming at sustainable farming. In conclusion, the differences of sustainability observed between the two farming systems were mainly due to the far lower marketable yield recorded in the OS vs the CS. Therefore, the priority future challenge of organic processing tomato farming should be the reduction of the yield gap between the OS and the CS, through the development of both new genotypes and innovative management methods, designed to reduce the gap, but not increasing the environmental impact on the agroecosystem. Highlights: Pesticide and fungicide applications have the highest impact in the OS. Soil tillage has the highest impact in the CS. One ton of marketable tomato fruit has still a lower carbon footprint in the CS than OS. One ha of processing tomato has less impact in the OS than CS. More hectares are needed to reach the same food production in the OCS respect the CS.